2007
DOI: 10.1007/s12013-007-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling and glucose transport in insulin resistant human skeletal muscle

Abstract: Insulin increases glucose uptake and metabolism in skeletal muscle by signal transduction via protein phosphorylation cascades. Insulin action on signal transduction is impaired in skeletal muscle from Type 2 diabetic subjects, underscoring the contribution of molecular defects to the insulin resistant phenotype. This review summarizes recent work to identify downstream intermediates in the insulin signaling pathways governing glucose homeostasis, in an attempt to characterize the molecular mechanism accountin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 108 publications
1
89
0
Order By: Relevance
“…These defects have been proposed to be largely regulated at the level of post-receptor signaling pathways. 29,30 Although the IL-18 resistance reported in this study is an immunological phenomenon, a tempting hypothesis (that remains to be demonstrated) is that a similar resistance to the metabolic effects of IL-18 is also present. Because the low expression of IL-18 receptors on human leukocytes precludes the reliable assessment of the molecules by flow cytometry, we assessed the mRNA expression of IL-18Ra and b by quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 76%
“…These defects have been proposed to be largely regulated at the level of post-receptor signaling pathways. 29,30 Although the IL-18 resistance reported in this study is an immunological phenomenon, a tempting hypothesis (that remains to be demonstrated) is that a similar resistance to the metabolic effects of IL-18 is also present. Because the low expression of IL-18 receptors on human leukocytes precludes the reliable assessment of the molecules by flow cytometry, we assessed the mRNA expression of IL-18Ra and b by quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 76%
“…This phenomenon includes insulin-independent [12] and insulindependent glucose clearance [14] as has been demonstrated in humans at risk of diabetes. Insulin action is not solely restricted to GLUTs regulation, but also to glucose homeostasis through hepatic glucose production suppression and stimulation of peripheral combustion [15].…”
Section: General Overview Of Type 2-diabetes Mellitus (T2dm)mentioning
confidence: 80%
“…GLUTs mediate insulin-stimulated glucose uptake in these organs and tissues by a mechanism involving translocation between cellular compartments. GLUT isoforms expression is regulated by insulin and other factors such as hypoxemia, oxidative phosphorylation and osmotic stresses [12].…”
Section: General Overview Of Type 2-diabetes Mellitus (T2dm)mentioning
confidence: 99%
See 1 more Smart Citation
“…In insulin resistant states, such as type 2 diabetes and obesity, insulin stimulated glucose disposal in skeletal muscle is markedly impaired [22][23][24][25][26][27][28]. The decreased insulin-stimulated glucose uptake is due to impaired insulin signaling, and multiple post receptor intracellular defects, including impaired glucose transport and glucose phosphorylation, and reduced glucose oxidation and glycogen synthesis [29][30][31][32].…”
Section: Skeletal Muscle Insulin Resistancementioning
confidence: 99%